Catalyst for removing oxygen from fluid containing hydrogen

By introducing Boehmite into the catalyst and combining gamma aluminum oxide and palladium, a high-activity and low-cost catalyst was developed, which solved the problem of insufficient activity of existing catalysts when removing oxygen in hydrogen, and achieved efficient hydrogen purification.

JP2025058762APending Publication Date: 2025-04-09JGC CATALYSTS & CHEMICALS LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023168899
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

The existing catalysts are insufficient in removing oxygen from hydrogen and have high costs, so it is necessary to develop a high-active and low-cost catalyst.

Method used

Using a catalyst consisting of gamma aluminum oxide, Boehmite and palladium (Pd), the content of Boehmite is determined by FT-IR spectroscopy to ensure its content in the catalyst is in the range of 0.5 to 2.0.

Benefits of technology

The catalyst exhibits high activity when removing oxygen from hydrogen, and can reduce the amount of use while maintaining high deoxygenation activity, and is suitable for industrial-scale hydrogen purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058762000001_ABST
    Figure 2025058762000001_ABST
Patent Text Reader

Abstract

To provide a catalyst with high activity for removing oxygen from a fluid containing hydrogen.SOLUTION: The deoxygenation catalyst achieves high deoxygenation activity by using a carrier that contains a trace amount of boehmite along with γ-alumina, in a catalyst where palladium is dispersed on a γ-alumina carrier. The amount of boehmite is preferably such that the ratio (I1500 / I1630) of the intensity (I1500) of an absorption band derived from boehmite to the intensity (I1630) of an absorption band derived from γ-alumina in the FT-IR spectrum is in the range of over 0.5 to 2.0.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for removing oxygen from a hydrogen-containing fluid. [Background technology]

[0002] Hydrogen can be produced from a variety of resources, and is therefore expected to be an energy source that can help reduce energy supply and procurement risks. Hydrogen can also be used as a carbon-free energy source by combining the electrolysis of water using renewable energy, and fossil fuels with carbon dioxide storage and reuse technologies, and is therefore attracting attention as a material that will play an important role in achieving carbon neutrality.

[0003] Hydrogen can contain oxygen due to the production process, so gas purification technology is required to remove oxygen in order to produce high-purity hydrogen. Typical methods include using a separation membrane, using an adsorbent, or using a catalyst.

[0004] For example, Patent Document 1 discloses a method for removing oxygen contained in hydrogen using a catalyst in which a carrier made of silica or alumina supports an iron group metal, an oxide of a rare earth element, and a platinum group metal as a catalytic substrate. Patent Document 2 discloses a method for reacting hydrogen and oxygen using a catalyst containing a catalytic metal selected from palladium, platinum, rhodium, and / or iridium arranged on a porous carbonaceous support. Patent Document 3 discloses a method for removing oxygen from gas in the presence of a reducing substance using two types of catalysts.

[0005] As described above, various catalysts are known for removing oxygen from fluids containing hydrogen. However, these catalysts are generally expensive, and there has been a demand for catalysts with high deoxidizing activity in order to reduce the amount of these catalysts used. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 58-174239 [Patent Document 2] Japanese Patent Application Publication No. 58-216720 [Patent Document 3] JP 2008-95082 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a highly active catalyst for removing oxygen from a fluid containing hydrogen. [Means for solving the problem]

[0008] The present inventors have found that in a catalyst in which palladium is dispersed on a gamma-alumina carrier, a carrier containing a trace amount of boehmite together with gamma-alumina can provide high deoxidizing activity. The present invention is based on this finding.

[0009] Specifically, the present invention relates to a compound that contains γ-alumina, boehmite, and palladium, and is characterized in that the intensity of the absorption band derived from boehmite in the FT-IR spectrum (I 1500 ) and the intensity of the absorption band due to γ-alumina (I 1630 ) and the ratio (I 1500 / I 1630 ) is in the range of more than 0.5 and not more than 2.0. The catalyst of the present invention has high activity in removing oxygen from a fluid containing hydrogen. In the above range of the intensity ratio, the symbol "to" indicates that the lower limit is greater than 0.5 and the upper limit is 2.0. Effect of the Invention

[0010] The catalyst of the present invention has high activity in removing oxygen from a fluid containing hydrogen, and therefore the amount of the catalyst used can be reduced. [Brief description of the drawings]

[0011] [Figure 1]1 is an FT-IR spectrum of the catalyst of Example 1. [Diagram 2] 1 is an FT-IR spectrum of the catalyst of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Catalyst of the present invention] The catalyst of the present invention is characterized in that palladium is supported on alumina containing a trace amount of boehmite, mainly composed of gamma alumina. By containing a trace amount of boehmite, the activity of removing oxygen from a fluid containing hydrogen (deoxygenation activity) is increased compared to a catalyst in which palladium is supported on activated alumina (gamma alumina) (gamma alumina does not contain boehmite) as described in Patent Document 3. The catalyst of the present invention will be described in detail below.

[0013] In the catalyst of the present invention, a small amount of boehmite present on the surface of the γ-alumina forms palladium clusters with a small coordination number, which are believed to function effectively in deoxidizing activity.

[0014] The catalyst of the present invention is a catalyst in which palladium is dispersed in a carrier containing γ-alumina and boehmite. 2 O 3 It is a type of aluminum oxide represented by the formula: and shows an X-ray diffraction pattern derived from its crystal structure. Therefore, the presence or absence of γ-alumina can be determined by X-ray diffraction measurement.

[0015] Boehmite is a type of alumina hydrate represented by AlOOH, and shows an X-ray diffraction pattern derived from its crystal structure. However, since the amount of boehmite contained in the catalyst of the present invention is very small, the presence or absence of boehmite cannot be determined from the X-ray diffraction pattern. Therefore, in the present invention, the presence or absence of boehmite is determined using FT-IR spectrum measurement (Fourier transform infrared spectroscopy). If an absorption band derived from the Al-OH bond of boehmite is observed, it can be determined that boehmite is present. Specifically, the absorption band at 1450 cm -1 ~1550cm -1If an absorption band having a peak top in this range is observed, it can be determined that boehmite is contained.

[0016] Furthermore, in the catalyst of the present invention, the intensity of the absorption band derived from the Al-O bond of alumina (I 1630 ) and the intensity of the absorption band due to the Al-OH bond of boehmite (I 1500 The boehmite content was determined by determining the ratio of 1450 cm -1 ~1550cm -1 The intensity of the absorption band due to the Al-OH bond that has a peak top in the range (I 1500 ) and 1580cm -1 ~1680cm -1 The intensity of the absorption band due to the Al-O bond that has a peak top in the range (I 1630 ) and the ratio (I 1500 / I 1630 ) to determine the boehmite content.

[0017] Specifically, the catalyst of the present invention has the above ratio (I 1500 / I 1630 ) is in the range of more than 0.5 and not more than 2.0. In the catalyst of the present invention, this ratio (hereinafter sometimes referred to as the boehmite / alumina intensity ratio) is preferably in the range of 0.6 to 1.8, and more preferably in the range of 0.7 to 1.6. Since the boehmite / alumina intensity ratio is in the above range, the catalyst of the present invention has high deoxidizing activity.

[0018] The catalyst of the present invention has a high deoxidizing activity, which converts oxygen contained in hydrogen into water and removes it. This deoxidizing effect can be evaluated by the oxygen removal rate. Since the voltage of hydrogen changes depending on the amount of oxygen contained in it, the oxygen removal rate can be evaluated by comparing the voltage A of hydrogen using the catalyst with the voltage B of hydrogen without using the catalyst.

[0019] Specifically, the measurement voltage of 32 mass number (MN), which corresponds to the molecular weight of oxygen (=32 g / mol), is used as the standard, and the voltage A of hydrogen using a catalyst is measured, and the voltage B of hydrogen without a catalyst (blank) is measured. The ratio of these (measurement voltage A / measurement voltage B) is used to determine the proportion of residual oxygen, and the oxygen removal rate X (%) can be calculated using the following formula (1). Oxygen removal rate X (%) = 100 - (measurement voltage A / measurement voltage B) × 100 (1)

[0020] The alumina content (the total content of γ-alumina and boehmite) of the catalyst of the present invention is Al 2 O 3 In terms of conversion, the total content is preferably in the range of 70% by mass to 99.99% by mass, more preferably in the range of 80% by mass to 99.9% by mass, and particularly preferably in the range of 90% by mass to 99.9% by mass.

[0021] The catalyst of the present invention contains palladium. Palladium is a type of catalytically active component and promotes deoxygenation reaction. The palladium contained in the catalyst of the present invention is considered to be present in the form of clusters, and its coordination number is preferably 7 or less, more preferably 6 or less. When the coordination number of palladium is reduced, the electronic state of palladium in the palladium cluster is changed, which is considered to increase the deoxygenation activity.

[0022] The palladium content of the catalyst of the present invention is preferably in the range of 0.01% by mass to 5% by mass, more preferably in the range of 0.1% by mass to 3% by mass, and particularly preferably in the range of 0.1% by mass to 1% by mass, calculated as Pd based on the total mass of the catalyst. The catalyst of the present invention has high deoxidizing activity, so that the deoxidizing activity is unlikely to decrease even if the palladium content is reduced. Furthermore, the catalyst of the present invention preferably has a degree of dispersion of palladium in the range of 15% to 37%. Since the coordination number of palladium is controlled in the catalyst of the present invention, the deoxidizing activity can be kept high even with such a low degree of dispersion.

[0023] The catalyst of the present invention may contain any component in addition to γ-alumina, boehmite and palladium. For example, it may contain a promoter component, a binder component and the like. The promoter component may contain a platinum group element other than palladium, specifically, at least one element selected from rhodium, platinum, ruthenium and rhodium. When these elements coexist with palladium, the deoxidizing activity tends to be higher. In addition, the binder component may contain a conventionally known component such as silica, alumina, clay mineral and the like. When the binder component is contained, the strength of the catalyst of the present invention tends to be high, which is preferable from the viewpoint of handling when used as an industrial catalyst. The content of these components is preferably 25% or less, more preferably 17% or less, and particularly preferably 9% or less by mass, based on the total mass of the catalyst.

[0024] The surface area of ​​the catalyst of the present invention is 160 m 2 / g~300m 2 / g range is preferred, with 170m 2 / g~275m 2 / g is more preferred, and 170m 2 / g~250m 2 When the specific surface area of ​​the catalyst is in the above range, the catalyst has high deoxidizing activity.

[0025] The shape of the catalyst of the present invention may be spherical, columnar (including cylindrical and four-lobe) or similar. The size (the minimum length of the catalyst outer shape) is preferably in the range of 0.5 mm to 6 mm. If the size of the catalyst is small, the contact area with oxygen increases, and therefore the deoxidizing activity tends to be higher.

[0026] The catalyst of the present invention can remove oxygen from a hydrogen-containing fluid and can also convert para-hydrogen to ortho-hydrogen at the same time. Para-hydrogen and ortho-hydrogen are nuclear spin isomers of hydrogen and have different physical properties. In steady-state hydrogen (gaseous hydrogen), the ratio of ortho-hydrogen to para-hydrogen is 3:1. When this is converted to liquid hydrogen, the ratio of para-hydrogen increases and slowly approaches 0:100. In the process of liquid hydrogen returning to steady-state hydrogen, the ratio of para-hydrogen to ortho-hydrogen gradually returns to 3:1.

[0027] If hydrogen is used before the ratio of para-hydrogen to ortho-hydrogen has returned to 3:1, there is a concern that the difference in physical properties may affect instrumentation devices, etc. The catalyst of the present invention can remove the oxygen contained in the hydrogen and simultaneously convert para-hydrogen to ortho-hydrogen, making it particularly effective in a method for removing oxygen from hydrogen using liquid hydrogen as a raw material.

[0028] The catalyst of the present invention can be prepared, for example, by a production method including (1) a carrier preparation step, (2) a palladium supporting step, and (3) a reduction step.

[0029] The method for producing the catalyst of the present invention will be described in detail below as an example of a method including the above steps, although the method for producing the catalyst of the present invention is not limited to the following method.

[0030] [Support preparation process] In this step, a carrier containing gamma alumina and boehmite is prepared. Such a carrier can be prepared, for example, by calcining pseudo-boehmite at a specific temperature. Alternatively, an alumina exhibiting such properties may be selected from various commercially available aluminas and used as the carrier. This step will be described in detail below, taking as an example a method of calcining pseudo-boehmite at a specific temperature.

[0031] Pseudo-boehmite can be prepared, for example, by mixing a solution containing sodium aluminate with a solution containing aluminum sulfate. At this time, it is preferable to mix in a temperature range of 40°C to 80°C. Mixing in this temperature range promotes the production of pseudo-boehmite. Since the pseudo-boehmite obtained by this method is obtained in the form of a slurry dispersed or precipitated in the solution, it is preferable to separate it by a method such as filtration as necessary. In addition, unreacted sodium aluminate, aluminum sulfate, etc. can be removed by washing with hot water or the like during separation. Since the pseudo-boehmite separated in this way is in the form of a cake, it is preferable to dry it to make it into a powder.

[0032] The dried pseudo-boehmite is calcined in air at a temperature of 450°C to 550°C to obtain a carrier powder containing gamma alumina and boehmite. At this time, the amount of boehmite contained in gamma alumina can be adjusted to some extent by adjusting the calcination time. The calcination time is appropriately adjusted depending on the amount of boehmite, but is preferably within about 0.5 hours to 3 hours.

[0033] The carrier powder can also be molded into various shapes as needed, for example, into a sphere, a columnar shape (including a cylindrical shape and a four-lobe shape) or similar shapes using a conventional molding method.

[0034] [Palladium Supporting Step] In this step, palladium is supported on the carrier containing gamma alumina and boehmite prepared in the previous step. As a method for supporting palladium, a method of contacting the carrier with an aqueous solution in which palladium is dissolved can be used. For example, a spray supporting method in which an aqueous solution in which palladium is dissolved is sprayed onto the carrier to support the carrier, and an impregnation method in which the carrier is immersed in an aqueous solution in which palladium is dissolved can be used. When using the spray supporting method, the palladium content of the carrier can be adjusted by adjusting the amount of the aqueous solution to be sprayed and the concentration of palladium contained in the aqueous solution. Also, when using the impregnation method, the amount of the aqueous solution to be taken into the carrier is measured in advance, and the concentration of palladium is adjusted according to the amount, thereby adjusting the palladium content of the carrier.

[0035] In this step, it is preferable to dissolve a water-soluble palladium compound in water to prepare an aqueous solution of palladium. Examples of the water-soluble palladium compound include palladium chloride, palladium nitrate, and palladium acetate, and any of these may be used.

[0036] [Reduction step] In this step, the palladium supported on the carrier is reduced to metal. As a method for reducing palladium to metal, a gas phase reduction method or a liquid phase reduction method can be used. When using a gas phase reduction method, palladium is reduced to metal by contacting a reducing gas (e.g., hydrogen, etc.) with the carrier on which palladium is supported. When using a liquid phase reduction method, palladium is reduced to metal by contacting a carrier containing palladium with a solution containing a reducing compound such as hydrazine or formic acid. At this time, the reduction temperature is preferably in the range of 50°C to 150°C.

[0037] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples. Measurement methods, evaluation methods, and various measurements were performed as follows.

[0038] [1] X-ray diffraction measurements The catalyst obtained in each Example was pulverized in a mortar, and the resulting powder was used to carry out X-ray diffraction measurement under the following conditions. <Condition> X-ray diffraction equipment: MiniFlex600 (Rigaku Corporation) Radiation source: Cu-Kα radiation Acceleration voltage, current: 40 kV, 15 mA Receiving slit: 13mm Scan speed: 5.0° / min Step width: 0.01° Measurement range (2θ): 10~80°

[0039] [2] FT-IR measurement The catalyst obtained in each example was pulverized, and the obtained powder was used for FT-IR measurement under the following conditions. <Condition> FT-IR equipment: IRSprit-T, SurveyIR (manufactured by Shimadzu Corporation) Measurement mode: Absorbance Light source: Ceramic light source Measurement wave number region: Mid-infrared <Specifying the amount of boehmite> An FT-IR spectrum was created with absorbance on the vertical axis and wave number on the horizontal axis. -1 ~1550cm -1 The intensity of the absorption band derived from boehmite that has a peak top in the range of 1500 ) and 1580cm -1 ~1680cm -1 The intensity of the absorption band derived from alumina that has a peak top in the range (I 1630 ) and the ratio (I 1500 / I 1630 ) was used to determine the boehmite content.

[0040] [3] Composition analysis (Pd) The catalyst obtained in each example was pulverized to a powder. This powder was collected in a beaker, formic acid was added, and the mixture was heated. Aqua regia was then added and dissolved by heating to extract palladium. The residue was then separated by filtration, and the filtrate was collected. The filtrate was diluted with water, and the palladium content was measured using an ICP device (Agilent Technologies, Inc., 730ICP-OES, inductively coupled plasma optical emission spectrometry).

[0041] [4] Palladium dispersion Using the catalyst obtained in each Example, the degree of dispersion of palladium was measured under the following conditions. <Condition> Metal dispersion measuring device: BEL-METAL-1 (Microtrack BEL Co., Ltd.) Sample pretreatment: Hydrogen flow rate 50sccm, temperature 250℃, treatment time 3 hours Measurement gas composition: Carbon monoxide 10%, helium balance, flow rate 10sccm, temperature 50℃ Catalyst loading amount: 0.05~0.08g

[0042] [5] Palladium coordination number X-ray absorption spectra at the Pd K-absorption edge (24350 eV) were measured by the transmission method using an X-ray absorption spectrometer (Rigaku R-XAS Looper). The X-ray tube was equipped with a W target and a W filament, and the applied voltage and tube current were 40 kV and 30 mA, respectively. Ge(840) was used as the analyzing crystal, and a Xe gas-filled proportional counter and a scintillation detector were used as the pre-sample and post-sample detectors, respectively. The average coordination number of palladium was obtained using Rigaku's REX-2000 software for analysis.

[0043] [6] Oxygen scavenging activity evaluation The catalyst obtained in each Example was evaluated for oxygen removal activity under the following conditions. <Condition> Evaluation equipment: BEL-CAT A, BEL-MASS (Microtrack BEL Co., Ltd.) Evaluation gas composition: Hydrogen 5,000ppm, oxygen 500ppm, nitrogen balance GHSV: 5,000h -1 Catalyst amount: 0.5mL Evaluation temperature: 120℃ Evaluation time: 12 hours <Evaluation method> The measurement voltage of 32 mass number (MN), which corresponds to the molecular weight of oxygen (=32 g / mol), was used as the standard, and the oxygen removal rate X (%) was determined by the following formula (1) based on the measurement voltage A of hydrogen using a catalyst and the measurement voltage B of hydrogen without a catalyst (blank). Oxygen removal rate X (%) = 100 - (measurement voltage A / measurement voltage B) × 100 (1)

[0044] [7] Para-ortho conversion activity About 0.3 mL of the catalyst obtained in the example was packed into a reaction tube with an inner diameter of 3.6 mm, and the temperature of the catalyst packed bed was adjusted to 50°C under a flow of He gas at 130 cc / min. Then, compressed hydrogen was used to convert a part of the ortho-hydrogen contained in the compressed hydrogen into para-hydrogen, and hydrogen was then passed through the catalyst packed bed. The hydrogen that passed through the catalyst bed was passed through an activated alumina column to separate ortho-hydrogen and para-hydrogen. The ortho-hydrogen and para-hydrogen that passed through the column were passed through a copper oxide column to convert them into water, and the chart was recorded with a TCD detector. The first peak detected in the obtained chart was regarded as para-hydrogen, and the second peak detected as ortho-hydrogen, and the ratio of the area of ​​the peak attributed to para-hydrogen to the total value of the areas of the respective peaks (Outlet) was calculated. In addition, the ratio of the peak area attributed to para-hydrogen was calculated in the same manner for hydrogen before passing through the catalyst bed (Inlet), and the difference Δ between this Inlet and Outlet (difference Δ=Inlet-Outlet) was regarded as the activity of para-hydrogen.

[0045] Example 1 [Support preparation process] A 100L steam jacketed tank is filled with Al. 2 O 39.09 kg of a 22% by mass aqueous sodium aluminate solution was added, diluted with pure water to 40.00 kg, and then 60.0 g of 99% by mass sodium gluconate (manufactured by Fuso Chemical Co., Ltd.) was added and heated to 60°C while stirring to prepare a 5% by mass aqueous sodium aluminate solution (L1). 2 O 3 An aqueous aluminum sulfate solution (L2) was prepared by diluting 14.29 kg of an aqueous aluminum sulfate solution (converted to 7% by mass) with 25.71 kg of ion-exchanged water and heating the resulting aqueous aluminum sulfate solution to 60°C.

[0046] The aqueous solution of sodium aluminate (L1) was stirred while the aqueous solution of aluminum sulfate (L2) was added thereto over a period of 10 minutes to prepare a pseudo-boehmite slurry. The pseudo-boehmite slurry was aged at 60°C for 60 minutes while stirring, and then dehydrated using a flat filter. The filtration residue was then washed with warm water at 60°C to obtain a washed cake.

[0047] The washed cake was dried in a tray dryer at 120° C. for 16 hours, and then calcined in a muffle furnace at 480° C. for 2 hours to obtain a support powder.

[0048] The carrier powder was mixed in a Henschel mixer while gradually adding ion-exchanged water, and kneaded until it became clay-like. This clay-like carrier powder was extruded into a 3 mm cylindrical shape using an extrusion molding machine. Then, the corners were rounded off using a Marmemerizer to obtain a spherical molded body (diameter 3 mm). The obtained spherical molded body was dried at 120°C for 16 hours to obtain a carrier.

[0049] [Palladium Supporting Step] 2.54 g of palladium chloride (manufactured by Kojima Chemical Co., Ltd.) was dissolved in 300 g of ion-exchanged water. 300 g of the carrier obtained in the above step was added to the palladium chloride solution and stirred.

[0050] [Reduction step] The temperature of the above-mentioned palladium chloride solution containing the carrier was adjusted to 60°C, and formic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added in an amount 5 times by mole relative to palladium, and reduction treatment was carried out at 60°C for 1 hour. After completion of reduction, the solid matter was separated. This solid matter was thoroughly washed with warm water and dried at 120°C to obtain a catalyst.

[0051] The catalyst obtained was subjected to the measurements and evaluations [1] to [6] above. The results are shown in Table 1. The absorption spectrum obtained by the FT-IR measurement in [2] above is shown in Figure 1. Furthermore, the catalyst was subjected to the evaluation in [7] above. The results are shown in Table 2.

[0052] Example 2 A catalyst was obtained in the same manner as in Example 1, except that 0.51 g of palladium chloride was dissolved in 300 g of ion-exchanged water. The obtained catalyst was subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0053] Example 3 A catalyst was obtained in the same manner as in Example 1, except that 5.10 g of palladium chloride was dissolved in 300 g of ion-exchanged water. The obtained catalyst was subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0054] Comparative Example 1 A gamma-alumina boehmite support having an FT-IR of 0.5 was obtained in the same manner as in Example 1, except that in the support preparation step, the washed cake was dried in a box dryer at 120°C for 16 hours and then calcined in a muffle furnace at 800°C for 2 hours. A catalyst was produced using this support in the same manner as in Example 1. The obtained catalyst was subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1. The absorption spectrum obtained by the FT-IR measurement in [2] above is shown in Figure 2.

[0055] Comparative Example 2 In the carrier preparation step, the washed cake was dried in a box dryer at 120°C for 16 hours, and then calcined in a muffle furnace at 1100°C for 2 hours, in the same manner as in Example 1, to obtain an α-alumina carrier having an FT-IR of 0.1. Using this carrier, a catalyst was produced in the same manner as in Example 1. The obtained catalyst was subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0056] Comparative Example 3 A catalyst was obtained in the same manner as in Example 1, except that 17.25 g of a chloroplatinic acid solution (Tanaka Kikinzoku Kogyo Co., Ltd.) was used instead of 2.54 g of palladium chloride (Kojima Chemical Co., Ltd.). The obtained catalyst was subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0057] Comparative Example 4 Activated carbon (Osaka Gas Chemicals, G 2X A catalyst was obtained in the same manner as in Example 1, except that 1,4-dichlorophenyl ether was used. The obtained catalyst was subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0058] [Table 1]

[0059] [Table 2]

Claims

1. Contains gamma alumina, boehmite and palladium, The intensity of the absorption band due to boehmite in the FT-IR spectrum (I 1500 ) and the intensity of the absorption band due to γ-alumina (I 1630 ) and the ratio (I 1500 / I 1630 ) is in the range of more than 0.5 to 2.0 or less, A catalyst for removing oxygen from a hydrogen-containing fluid.

2. 2. The catalyst according to claim 1, wherein the coordination number of said palladium is 7 or less.

3. 3. The catalyst according to claim 2, wherein the dispersion of said palladium is in the range of 15% to 37%.

Citation Information

Patent Citations

  • Three-component catalyst for removing oxygen from gas containing oxygen consisting essentially of gaseous hydrogen and its production

    JP1983174239A

  • Removal of oxygen

    JP1983216720A

  • Method for removing oxygen

    JP2008095082A